2022
DOI: 10.1038/s41419-022-04637-8
|View full text |Cite
|
Sign up to set email alerts
|

The pro-tumorigenic activity of p38γ overexpression in nasopharyngeal carcinoma

Abstract: It is urgent to identify and validate biomarkers for early diagnosis and efficient treatment of nasopharyngeal carcinoma (NPC). Recent studies have proposed p38 gamma (p38γ) as a cyclin-dependent kinase (CDK)-like kinase that phosphorylates retinoblastoma (Rb) to promote cyclins expression and tumorigenesis. Here the Gene Expression Profiling Interactive Analysis (GEPIA) database and results from the local NPC tissues demonstrate that p38γ is significantly upregulated in NPC tissues, correlating with poor over… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
40
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 19 publications
(44 citation statements)
references
References 37 publications
4
40
0
Order By: Relevance
“…Zhu et al found a close association between ALDH1B1 expression and prognosis of locally-advanced NPC ( Zhu et al, 2022 ). In addition, studies have suggested that p38γ is a key oncogene and an important therapeutic target for NPC ( Yin et al, 2022 ), and that Circ_0028007 promotes NPC progression by adsorbing miR-656-3p and increasing ELF2 expression ( Ma and Li, 2022 ). These findings indicate that targeted therapy for NPC is a promising area for further research.…”
Section: Introductionmentioning
confidence: 99%
“…Zhu et al found a close association between ALDH1B1 expression and prognosis of locally-advanced NPC ( Zhu et al, 2022 ). In addition, studies have suggested that p38γ is a key oncogene and an important therapeutic target for NPC ( Yin et al, 2022 ), and that Circ_0028007 promotes NPC progression by adsorbing miR-656-3p and increasing ELF2 expression ( Ma and Li, 2022 ). These findings indicate that targeted therapy for NPC is a promising area for further research.…”
Section: Introductionmentioning
confidence: 99%
“…Quantitative real time-PCR (qPCR), Western blotting and co-immunoprecipitation (Co-IP) was described early as well 30 , 31 . CellROX staining of ROS content, tissue/cellular ATP contents and the mitochondrial complex I activity were measured using the described protocols 29 , 37 . Figure S1 listed the uncropped blotting images.…”
Section: Methodsmentioning
confidence: 99%
“…Other functional assays , including the caspase-3 activity assay, Western blotting assay, mRNA detection by qRT-PCR were described in early studies [ 22 , 31 ]. Measuring ATP contents was described previously [ 40 ]. The intensity of lipid peroxidation in cell and tissue lysates was examined through a thiobarbituric acid reactive substance (TBAR) kit (Cayman Chemical, MI).…”
Section: Methodsmentioning
confidence: 99%